2021
DOI: 10.1038/s41438-021-00561-8
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-induced DNA demethylation of metal transporters and antioxidant genes alleviates lead stress in radish plants

Abstract: Melatonin (MT) is a tryptophan-derived natural product that plays a vital role in plant response to abiotic stresses, including heavy metals (HMs). However, it remains elusive how exogenous MT mediates lead (Pb) accumulation and detoxification at the methylation and transcriptional levels in radish. In this study, decreased Pb accumulation and increased antioxidant enzyme activity were detected under MT treatment in radish. Single-base resolution maps of DNA methylation under Pb stress (Pb200) and Pb plus MT t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Nipponbare), and more hypermethylated genes were found than hypomethylated ones [85]. The level of total methylation in radish and soybean (Glycine max) increased after Cd exposure with a significant dose-dependent relationship [86,87]. Methylation levels in the roots of heavy metal tolerant plants is significantly higher than that of sensitive plants, comparing clover (Trifolium repens L., sensitive species) with hemp (Cannabis sativa L., partial tolerant) [88], as well as Ni-tolerant Noccaea caerulescens with Ni-susceptible A. thaliana [89].…”
Section: Dna Methylation and Heavy Metal Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Nipponbare), and more hypermethylated genes were found than hypomethylated ones [85]. The level of total methylation in radish and soybean (Glycine max) increased after Cd exposure with a significant dose-dependent relationship [86,87]. Methylation levels in the roots of heavy metal tolerant plants is significantly higher than that of sensitive plants, comparing clover (Trifolium repens L., sensitive species) with hemp (Cannabis sativa L., partial tolerant) [88], as well as Ni-tolerant Noccaea caerulescens with Ni-susceptible A. thaliana [89].…”
Section: Dna Methylation and Heavy Metal Stressmentioning
confidence: 99%
“…Transposable elements are one of the most heavily methylated DNA regions and were shown to play a role in Al stress responses in tolerant accessions of barley [94]. Furthermore, it was also found that a high density of TEs were strongly methylated in radish under Pb treatment [86]. Gene expression controlled by DNA methylation is another epigenetic response to heavy metal stress.…”
Section: Dna Methylation and Heavy Metal Stressmentioning
confidence: 99%
“…Overexpression of TaZnF in A. thaliana significantly increased tolerance to heat and cold stress as well as promoted early flowering [ 16 ]. Similarly, there are numerous studies in many plant species that evidenced the pivotal role of MTs in uptake, sequestration, translocation and detoxification of toxic HMs including cadmium (Cd) [ 17 ], chromium (Cr) [ 18 ], lead (Pb) [ 19 ], As [ 20 ], cobalt (Co) and zinc (Zn) [ 21 ] (for more details, see Section 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, melatonin treatment balances endogenous GA and ABA levels and improves thiol-mediated detoxification in two indica rice. Furthermore, melatonin reduces Pb damage in radish plants via DNA demethylation of metal transporters and antioxidant genes ( Tang et al, 2021 ).…”
Section: Roles Of Melatonin In Plant Abiotic Stress Responsesmentioning
confidence: 99%